Development of web-based material on bioinformatics / Kamaruddin Mamat and Farida Zuraina Mohd Yusof - Mamat, Kamaruddin; Mohd Yusof, Farida Zuraina (2006)
This development of a web-based material on Bioinformatics aim is to design a learning package via Internet. The gaining popularity and the wide use of Internet have realized the importance of WWW as an educational medium. Basically, there are jive main pages that have been interconnected which are the Home Page. FAQ Page. Information Page, Tutorial Page and Links Page. Home Page is the page that will be seen first, it acts as the main menu of the website. The FAQ Page would showcase all the basic questions the user might have, and it will give definitions in an easy to understand method. This page would also gather all the doubts that the user might have, where they could send it to the Webmaster for reply in the future. Information page is where one can get all the information needed to have a deeper understanding about the topic. There is also a test on Bioinformatics available here. At the Tutorial Page, the user can get examples on Sequence Analysis, which provides a chance to get hand son experience in using advanced programs in the same way as modern biologists frequently do. It shows how the optimal aligment of two proteins stored in a database can be performed over the Internet. This example also demonstrates how fast and relatively easy existing databases can be searched. The biggest advantage of these databases is of course, that they are accessible over the Internet using the World Wide Web as graphical user interface. All the programs for user search are usable over the Internet. The advantage of having this website is it gives a high level understanding to students anywhere as long as there is an internet connection available. In future. it is expected that the use of WWW will surpass the standard that is being used today. Furthermore, universities and schools of the future might only exist in virtual reality where classes will be conducted through WWW with the use of web-based material.